2019
DOI: 10.1089/acm.2019.0167
|View full text |Cite
|
Sign up to set email alerts
|

Brain Plasticity and Neurophysiological Correlates of Meditation in Long-Term Meditators: A18Fluorodeoxyglucose Positron Emission Tomography Study Based on an Innovative Methodology

Abstract: Objective: Previous studies evaluating neurophysiological correlates of long-term meditation are constrained by some methodological limitations. The objective of this study was to measure changes in the regional cerebral glucose metabolism during meditation using a novel methodological approach. Design: The present study was a part of a larger, nonrandomized, single-center open-label study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…These areas are also found to be active on fMRI during meditation process by several studies, as concluded in the meta-analysis by Boccia et al (2015). Magan et al (2019) in the FDG-PET 18-fluorodeoxyglucose-(FDG-PET) study of 12 long term meditators showed the activation of the fronto-parieto-temporal regions. Even though this study is based on short-term meditators, it is interesting to see how quickly the energy metabolism changes.…”
Section: Cerebral Magnesium and Phmentioning
confidence: 75%
See 1 more Smart Citation
“…These areas are also found to be active on fMRI during meditation process by several studies, as concluded in the meta-analysis by Boccia et al (2015). Magan et al (2019) in the FDG-PET 18-fluorodeoxyglucose-(FDG-PET) study of 12 long term meditators showed the activation of the fronto-parieto-temporal regions. Even though this study is based on short-term meditators, it is interesting to see how quickly the energy metabolism changes.…”
Section: Cerebral Magnesium and Phmentioning
confidence: 75%
“…Magan et al ( 2019 ) in the FDG-PET 18-fluorodeoxyglucose-(FDG-PET) study of 12 long term meditators showed the activation of the fronto–parieto–temporal regions. Even though this study is based on short-term meditators, it is interesting to see how quickly the energy metabolism changes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, pranayama emphasizes long exhalation and conscious slow breathing that positively modulates the parasympathetic nervous system ( 33 , 34 ). Yoga-meditation influences different areas of the brain, specifically on the right side of the brain, which might influence the neuroendocrinological axis ( 30 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention is delivered to a group of six to eight participants at a time, allowing them ample time to interact with the experts (medical doctors, yoga experts, and dietitians). The YBLI used in this study has been pretested and published previously (21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Mediation can be practiced by focusing on an object or event (Focused Attention) or, in a more advanced modality, without recourse to this tactic (Open Monitoring) [18]. Meditation has been reported to offer multiple psychoneurophysiological benefits, including: reduction in stress and inflammation [19]; increase in attentional networks at neural level [20], enhancement of explicit functions of parts of the right hemisphere [21], and the alleviation of psychological distress in cancer patients [22]. The American Heart Association considers meditation as an adjunct to guideline-directed cardiovascular risk reduction [23].…”
Section: Introductionmentioning
confidence: 99%